Rethinking attitudes and social psychology – Issues of function, order, and combination in subject-side and object-side assessments in natural settings. Issue 3 (2nd July 2020) - Potter, Jonathan; Hepburn, Alexa; Edwards, Derek
ABSTRACT: This paper overviews limitations in both the way attitude function has been conceptualized in social psychology, and in the empirical basis for the claims made. We suggest that the premise that attitudes are expressed for cognitive/motivational reasons is an untested artefact of the methodological procedures commonly used. In contrast, an investigation of 'attitudes' in the wild (assessments, evaluations, judgements) is offered as an alternative pathway to address questions of function. The analytic core of the paper is the analysis of a collection of interactional examples where an Object-side assessment (e.g. 'this soup is lovely') is issued in combination with a Subject-side assessment (e.g. 'I love this soup'). We investigate what is achieved by combining O-side and S-side assessments: why use an O-side assessment and then an S-side assessment? Or, why use an S-side assessment and then an O-side? We show that (a) O-side and S-side assessments support different actions; (b) the combination manages world and speaker issues in a single package; (c) the combination of O-side and S-side can be hearably complete; (d) O-side first, S-side second can be a resource for building (on) affiliation; (e) S-side first, O-side second can be a platform for continued dispute. Programmatic work on the function of assessments is proposed.